Democratic dialogue a handbook for practitioners - Pruitt, Bettye; Thomas, Philip; United Nations Development Programme; International Institute for Democracy and Electoral Assistance; Canadian International Development Agency; Organization of American States (Washington, D.C. Insitute for Democracy and Electoral Assistance, 2007)
"This Handbook, sponsored jointly by International IDEA, the United Nations Development Programme (UNDP), the Organization of American States (OAS) and the Canadian International Development Agency (CIDA), offers a comprehensive overview of the use of dialogue processes to address societal challenges in an inclusive, democratic way that engages a broad range of actors in bringing about positive change. It is addressed to people actively or potentially engaged in doing dialogue work--organizing, sponsoring, promoting, or facilitating dialogue processes within their institutions and societies. Most importantly, it is thoroughly grounded in the experience of dialogue practitioners from around the world. The Handbook provides a conceptual framework that speaks to critical questions: 'Why dialogue?', 'What is dialogue?' and 'How does dialogue contribute to positive change?'. It offers a detailed guide to putting these concepts into practice, offering practical guidance and concrete examples from the field for each step: exploring whether a dialogue process is appropriate in the context; designing and then implementing a dialogue process; and conducting a meaningful process of monitoring and evaluation throughout. A third major part of the book anchors all of this information in the reality of three fully developed case studies showing different approaches in different regions--Latin America, Africa and Asia. In two appendices, the Handbook also provides a comparative overview of more than 30 cases and a guide to the rich array of dialogue processes and process tools that practitioners can consider for use, or just for inspiration."--P. 4 of cover.
The handbook is the result of a joint initiative (Institute for Democracy and Electoral Assistance, the Organization of American States, CIDA and UNDP) to provide decision-makers and practitioners with a practical guide on how to design, facilitate and implement dialogue processes.
At head of title: International Institute for Democracy and Electoral Assistance, IDEA; Canadian International Development Agency = Agence canadienne de dé́veloppement; Organization of American States; UNDP.
Includes bibliographical references (p. 225-238).
Keywords: Democratization; Diplomacy; Negotiation -- Political aspects; Intercultural communication; Communication -- Political aspects; Social change -- Political aspects; Consensus (Social sciences); Peace-building.